Comparing charcoal and wood-burning cookstoves - Wartluft, Jeffrey L (Volunteers in Technical Assistance ArlingtonUS, 1984)
Evaluates the performance of cookstoves generally used by Montserrat households. Records the results of tests of specially designed trial and wood-burning stoves. Such stoves were tested for efficiency, economy, and acceptability. Appendixes include cookstove designs, water boiling test procedures and kitchen performance test data sheet.